LabVIEW-based frequency and voltage control of synchronous generators - Fu, Meng. (2013)
Continuing from Optimal Power Flow (OPF) and Economic Dispatch (ED) developed by the Microgrid Energy Management System (MEMS) project team, this project aims to improve the load frequency and voltage control of synchronous generator that can fully implement Automatic Generation Control in MEMS. This small distribution generation system is built with a LabVIEW-based program to monitor and control the synchronous generator. In this report, it will discuss on the control hardware components for the system, such as the Automatic Voltage Regulator (AVR) and Automatic Gen-set Controller (AGC). A synchronous generator with a prime mover motor performs as a local generation for the system. Furthermore, the governor and AVR implement the Load Frequency Control (LFC) and voltage control respectively. On the aspects of software, an automatic voltage control panel is developed for AVR. It is designed to stabilize the terminal voltage without variation of reactive power load. The AVR system is integrated with existing Optimal Power Flow (OPF) in order to achieve power losses reduction. The AGC system only succeeds in voltage control. Due to some constraint, it is not fully test on the LFC. In the further improvement, the LFC need to be designed to stabilize frequency.